Variasi Makna Puasa Dalam Al-Quran (Studi Semantik al-Quran) - Nurfadzilla Putri Putri; WALI RAMADHANI RAMADHANI (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2023)
AbstractThis article discusses the various meanings of fasting or shaum in the Koran. This research departs from the difference in the meaning of shaum between QS. Maryam verse 26 and QS. Al-Baqarah verse 183. Through the analytical descriptive data analysis method with the semantic approach of the Koran, the author tries to analyze in an inclusive and comprehensive manner related to the variations in the meaning of fasting in the Koran. Linguistically, fasting means refraining from something or leaving it, be it refraining from eating, talking or walking. This meaning contained in QS. Maryam verse 26. However, functionally in the Koran, fasting does not only mean withholding, but also the part of worship that must be carried out with the provisions of the applicable Shari'a (QS. Al-Baqarah verses 183-185, 187), and also has an alternative meaning expiation or ransom for prohibited acts (QS. Q.S Al-Baqarah verse 196, Q.S An-Nisa verse 92, Q.S Al-Maidah verse 89).